2013
DOI: 10.1177/1359104513499355
|View full text |Cite
|
Sign up to set email alerts
|

Improving antenatal risk assessment in women exposed to high risks

Abstract: Antenatal substance use and related psychosocial risk factors are known to increase the likelihood of child protection involvement; less is known about the predictive nature of maternal reflective functioning (RF) in this population. This preliminary study assessed psychosocial and psychological risk factors for a group of substance dependent women exposed to high risks in pregnancy, and their impact on child protection involvement. Pregnant women on opiate substitution treatment (n = 11) and a comparison grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 74 publications
0
22
0
Order By: Relevance
“…In addition, findings by Stacks et al (2014) showed that maternal reflective functioning was associated with parenting sensitivity which, in turn, was associated with infant attachment security, thus replicating previous findings (Grienenberger et al, 2005). Only Perry et al (2015) did not find any significant relationship between PI-RF, PDI-RF and maternal emotional availability in a study that, however, had some methodological flaws concerning, above all, sample size and significant delay in follow-up regarding some mother-child dyads.…”
Section: Resultsmentioning
confidence: 83%
“…In addition, findings by Stacks et al (2014) showed that maternal reflective functioning was associated with parenting sensitivity which, in turn, was associated with infant attachment security, thus replicating previous findings (Grienenberger et al, 2005). Only Perry et al (2015) did not find any significant relationship between PI-RF, PDI-RF and maternal emotional availability in a study that, however, had some methodological flaws concerning, above all, sample size and significant delay in follow-up regarding some mother-child dyads.…”
Section: Resultsmentioning
confidence: 83%
“…These findings are in line with the majority of existing studies indicating that the presence of risk factors negatively affects mothers’ RF ability, with HR women have lower RF and more negative mental representations (Huth‐Bocks et al., ; Leigh, ; Seng & Prinz, ; Theran et al., ). An exception to the rule is a study by Perry et al (), who found similar prenatal RF levels for both HR and LR women. However, their sample size was limited and consisted mainly of multiparous women.…”
Section: Discussionmentioning
confidence: 92%
“…These factors could affect prenatal maternal RF. Maternal characteristics that have been negatively related to RF include psychiatric illness (Fonagy & Luyten, ; Levinson & Fonagy, ; Perry, Newman, Hunter, & Dunlop, ; Toth, Rogosch, & Cicchetti, ), substance use during pregnancy (Pajulo et al., ), single parenthood (Huth‐Bocks, Levendosky, Bogat, & Von Eye, ), unavailability of support from family and friends (Larney, Cousens, & Nunn, ; Sadler et al., ; Smith, ), scarcity of material resources (e.g., regarding housing or financially), and low educational attainment (Pajulo, Helenius, & Mayes, ; Rosenblum, McDonough, Sameroff, & Muzik, ; Sadler et al., ; Theran et al., ; Vrieze, ). These factors also have been used to define risk status with respect to child sociobehavioral outcomes (World Health Organization, ).…”
mentioning
confidence: 99%
“…In one study, pregnant woman at high risk (defined as mental health problems, substance use, or social problems) had lower P-PRF than did pregnant women at low risk, and the presence of multiple risk factors was associated with lower P-PRF scores [40]. In contrast, another study found that prenatal PRF was not associated with psychosocial risk factors or involvement with child protection services among women on opiate substitution treatment or in the comparison group [41]. To inform our understanding of potential similarities and differences between the concepts of MFB and prenatal parental reflective functioning, more evidence is needed.…”
Section: Prenatal Parental Reflective Functioning and Mother-fetal Bomentioning
confidence: 96%